A study of microsporidiosis in corneal scrapings of keratitis patients referring to Farabi Eye Hospital, Tehran, Iran in 2013-14 - MirMostafa Ghamiloui; Zarrintaj Valadkhani; Firoozeh Rahimi (Current Medical Mycology, 2015)
Background and Purpose: Microsporidiosis is one of the emerging and opportunistic infections, which causing various clinical symptoms in humans. The prevalence of this infection varies, depending on the infected organ, diagnostic methods, and geographical conditions. In the present study, we aimed to investigate microsporidial keratitis in patients referring to Farabi Eye Hospital Tehran, Iran in 2013-14. Materials and Methods: Two scraping samples were collected from 91 keratitis patients, five cases had prior history of receiving immune suppressive drugs. One of the two collected samples from each participant was used for Vero cell culture and the other was used for the preparation of Giemsa and Gram staining slides. After 30 days, the cells were scrapped and used for DNA extraction afterwards, nested polymerase chain reaction (PCR) detection method was applied. Primer pairs of small-subunit ribosomal RNA gene were designed by CLC Genomics workbench software to amplify all major microsporidian pathogens, as well as E. bieneusi , which was used as the positive control in this study. Results: The nested PCR showed negative results regarding the presence of microsporidia in the samples. Similarly, Giemsa and Gram staining slides did not detect any spores. Conclusion: The prevalence of human microsporidiosis ranges between 0% and 50%, worldwide. Based on all the negative samples in the present study, we can conclude that the prevalence of this infection among Iranian patients falls in the lower quartile. By gathering further evidence, researchers can take a step forward in this area and open new doors for the assessment of AIDS patients and users of immunosuppressive drugs.